2011
DOI: 10.1128/jcm.02595-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abbott RealTi m e CT/NG Assay in Comparison to the Roche Cobas Amplicor CT/NG Assay

Abstract: Several commercial methods exist for the molecular detection of Chlamydia trachomatis and Neisseria gonorrhoeae in clinical samples. Here we evaluated the performance characteristics of the newly FDAcleared Abbott RealTime CT/NG assay (where "CT" stands for Chlamydia trachomatis and "NG" stands for Neisseria gonorrhoeae) that uses the automated m2000 molecular platform. Results were compared to those of the Roche Cobas Amplicor CT/NG assay. A total of 926 cervical swab, 45 female urine, 6 male urethral swab, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 20 publications
2
39
1
Order By: Relevance
“…Similarly, Rockett et al (15) showed that the cobas CT/NG assay for C. trachomatis detected 94.5% of the FVU specimens found to be positive by the firstgeneration Amplicor test. These studies (14,15) suggest that the two newer second-generation assays are performing comparably to the first-generation tests with FVU samples.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Rockett et al (15) showed that the cobas CT/NG assay for C. trachomatis detected 94.5% of the FVU specimens found to be positive by the firstgeneration Amplicor test. These studies (14,15) suggest that the two newer second-generation assays are performing comparably to the first-generation tests with FVU samples.…”
Section: Discussionmentioning
confidence: 97%
“…Cheng et al (14) compared the RealTime CT/NG assay and the first-generation Amplicor CT/NG assay, showing very high levels of agreement for FVU specimens. Similarly, Rockett et al (15) showed that the cobas CT/NG assay for C. trachomatis detected 94.5% of the FVU specimens found to be positive by the firstgeneration Amplicor test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC STD Laboratory Diagnosis Guidelines recommend screening using highly sensitive and specific nucleic acid amplification assays (NAATs) (4), confirming that this class of testing is now considered the standard for the diagnosis of these infections. NAATs have been commercially available for the last 2 decades, and evidence of their performance characteristics is widely available (6,7,(10)(11)(12)(13)(14)(15)(16)(17). As chlamydia and gonorrhea screening programs continue to expand to meet the health care coverage benchmarks described by the U.S. Preventive Task Force (USPTF), the CDC (5), and the Healthcare Effectiveness Data and Information Set (HEDIS), clinical diagnostic laboratories will experience increased volumes.…”
mentioning
confidence: 99%
“…Current screening for this bacterial STI pathogen among infertile men and semen donors is strongly recommended, as it can cause serious reproductive complications in the recipients of semen donations and infection in their offspring (Peeling & Embree, 2005;Eley & Pacey, 2011 cervical specimens are currently available with far higher sensitivity than cell culture or antigen detection (Semeniuk et al, 2002;BĂ©bĂ©ar & de Barbeyrac, 2009). An increasing number of laboratories are now offering combinatorial NAATs for the diagnosis of both C. trachomatis and Neisseria gonorrhoeae infections (Gaydos et al, 2010;Hopkins et al, 2010;Rockett et al, 2010;Cheng et al, 2011;Kerndt et al, 2011). The Roche Diagnostics cobas CT/NG test, performed on the cobas 4800 system, is a new commercialized diagnostic assay using an automated workstation to isolate nucleic acids from clinical specimens and a real-time instrument for the detection of C. trachomatis and N. gonorrhoeae (Rockett et al, 2010;Taylor et al, 2012;Van Der Pol et al, 2012).…”
Section: Introductionmentioning
confidence: 99%